Movement towards transdiagnostic psychotherapeutic practices for the affective disorders. Issue 3 (29th June 2016) - Gros, Daniel F; Allan, Nicholas P; Szafranski, Derek D
Abstract : Evidence-based cognitive behavioural therapy (CBT) practices were first developed in the 1960s. Over the decades, refinements and alternative symptom foci resulted in the development of several CBT protocols/manuals for each of the many disorders, especially in the affective disorders. Although shown to be effective in highly trained providers, the proliferation of CBT protocols also has shown to demonstrate challenges in dissemination and implementation efforts due to the sheer number of CBT protocols and their related training requirements (eg, 6 months per protocol) and their related cost (eg, over US$2000 each; lost days/hours at work). To address these concerns, newer transdiagnostic CBT protocols have been developed to reduce the number of disorder-specific CBT protocols needed to treat patients with affective disorders. Transdiagnostic treatments are based on the notion that various disorder-specific CBT protocols contain important but overlapping treatment components that can be distilled into a single treatment and therefore address the symptoms and comorbidities across all of the disorders at once. 3 examples of transdiagnostic treatments include group CBT of anxiety, unified protocol for transdiagnostic treatment for emotional disorders and transdiagnostic behaviour therapy. Each transdiagnostic protocol is designed for a different set of disorders, contains a varied amount of CBT treatment components and is tested in different types of samples. However, together, these 3 transdiagnostic psychotherapies represent the future of CBT practice.